The use of group support systems in focus groups: Information technology meets qualitative research. - Klein, Esther E.; Tellefsen, Thomas; Herskovitz, Paul J. (Computers in Human Behavior, 2007)
This paper explores focus groups supported by group support systems (GSS) with anonymous interaction capability in two configurations: same time/same place and same time/different place. After reviewing the literature, we compare and contrast these anonymity-featured GSS-supported focus groups with traditional focus groups and discuss their benefits and limitations. We suggest directions for future research concerning GSS-supported focus groups with respect to technological implications (typing skills and connection speeds), national culture (high and low context; power distance), and lying behavior (adaptation of model of Hancock, J. T., Thom-Santelli, J., & Ritchie, T. (2004). Deception and design: The impact of communication technology on lying behavior. Proceedings of the 2004 conference on human factors in computing systems (pp. 129-134), whereby lying is a function of three design factors: synchronicity, recordability, and distributedness). Copyright (c) 2007 Elsevier Ltd